(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
Biochemical and stomatal studies were conducted on selected trees along Zaria-Kaduna highway to determine their pollution tolerance level. The sites were chosen to emphasize exposure to vehicular emission pollution (VEP) and non-exposure to vehicular emission pollutants (NEP). Biochemical parameters analyzed where based on the Air Pollution Tolerance Index (APTI) which prioritizes four biochemical parameters, namely ascorbic acid, total chlorophyll, leaf extract pH and relative water content (RWC), for pollution tolerance. Ascorbic acid and RWC were higher in plants at the polluted site with Mangifera indica showing the highest increase of 1.2mg/g while total chlorophyll decreased most significantly in Ficus polita of about 4.1mg/g. Results from stomata studies reveal a significant difference (P â‰¤ 0.05) in stomatal size and stomatal index for all the trees at the polluted sites. Stomata was generally found to significantly decrease in size or increase in density for plants at the polluted sites. Results computed for APTI show M. indica (24), Anarcardium occidentale (24.1), Eucalyptus cameldulensis (17.1) and Senna siamea (18.6) having the best APTI which indicate their possible tolerance to air pollution stress while Azadirachta indica (14.4), Ficus polita (13), G. arborea (9.4), T. catapa (15.2), Parkia biglobosa (13.4), and Tamarindus indica (9.9) were found to be sensitive. M. indica and A. occidentale had the best APTI indices which indicate that these plants could serve as sinks in absorbing air pollutants